Drivers of the extreme North Atlantic marine heatwave during 2023 - Matthew H. England; Zhi Li; Maurice F. Huguenin; Andrew E. Kiss; Alex Sen Gupta; Ryan M. Holmes; Stefan Rahmstorf (Nature, 2025)
Abstract North Atlantic Ocean circulation and temperature patterns profoundly influence global and regional climate across all timescales, from synoptic1 to seasonal2–4, decadal5, multidecadal6,7 and beyond8,9. During 2023, an extreme and near-basin-scale marine heatwave developed during Northern Hemisphere summer, peaking in July. The warming spread across virtually all regions of the North Atlantic, including the subpolar ocean, where a cooling trend over the past 50–100 years has been linked to a slowdown in the meridional overturning circulation10,11. Yet the mechanisms that led to this exceptional surface ocean warming remain unclear. Here we use observationally constrained atmospheric reanalyses alongside ocean observations and model simulations to show that air–sea heat fluxes acting on an extremely shallow surface mixed layer, rather than anomalous ocean heat transport, were responsible for this extreme ocean warming event. The dominant driver is shown to be anomalously weak winds leading to strongly shoaling (shallowing) mixed layers, resulting in a rapid temperature increase in a shallow surface layer of the North Atlantic. Furthermore, solar radiation anomalies made regional-scale warming contributions in locations that approximately correspond to some of the region’s main shipping lanes, suggesting that reduced sulfate emissions could also have played a localized role. With a trend towards shallower mixed layers observed over recent decades, and projections that this will continue into the future, the severity of North Atlantic marine heatwaves is set to worsen.